1986
DOI: 10.1530/jrf.0.0760349
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone pretreatment has a direct effect on GnRHinduced preovulatory follicles to determine their ability to develop into normal corpora lutea in anoestrous ewes

Abstract: In two experiments carried out during seasonal anoestrus, Romney Marsh ewes were treated with small-dose (250 ng) multiple injections of GnRH at 2-h intervals with and without progesterone pretreatment. In Exp. 1, 8/8 progesterone-primed ewes ovulated and produced functionally normal corpora lutea compared with 2/9 non-primed ewes. Follicles were recovered from similarly treated animals 18 or 28 h after the start of GnRH treatment (at least 14 h before the estimated time of the LH peak) and assessed in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

1987
1987
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 18 publications
(22 reference statements)
2
32
0
2
Order By: Relevance
“…(b) The injection of P4 (or progestagen treatment) performed some days (3-5) before introduction of rams had the same effect on suppression of short-lifespan CL, but did not delay the interval between male introduction and LH surge [5]. (c) A single injection of P4 in GnRH treated ewes without the ram effect, is able to restore CL of normal life span on the contrary to control ewes with no P4 treatment [30,60]. Thus, the initial hypothesis of an enlargement of the duration of the follicular phase after P4 treatment is probably not adequate and suggests that other mechanisms are working at the ovarian and/or uterine levels.…”
Section: How Exogenous P4 Acts To Completely Suppress Short Cycles? Imentioning
confidence: 96%
See 1 more Smart Citation
“…(b) The injection of P4 (or progestagen treatment) performed some days (3-5) before introduction of rams had the same effect on suppression of short-lifespan CL, but did not delay the interval between male introduction and LH surge [5]. (c) A single injection of P4 in GnRH treated ewes without the ram effect, is able to restore CL of normal life span on the contrary to control ewes with no P4 treatment [30,60]. Thus, the initial hypothesis of an enlargement of the duration of the follicular phase after P4 treatment is probably not adequate and suggests that other mechanisms are working at the ovarian and/or uterine levels.…”
Section: How Exogenous P4 Acts To Completely Suppress Short Cycles? Imentioning
confidence: 96%
“…The hypothesis of a seasonal difference in follicular composition is not supported by the results of Cahill et al [28,29] who did not find any difference in granulosa cell content of the follicle of the breeding season compared to the anoestrous season. On the contrary, the hypothesis of a difference in the evolution of the luteal cells between D0 and D4 is supported by the description of an inadequate luteal function due to poor response to the LH surge during the final maturation of the anoestrous follicle in ewes [30,32]. In rats and women, if intrafollicular concentration of P4 is low, luteal development is abnormal [33].…”
Section: Importance Of the CL Characteristics Issued From Male-inducementioning
confidence: 99%
“…The present results differ from those of previous studies in a number of important respects. First, we used hCG in preference to oLH, as Hunter et al (1986Hunter et al ( , 1988 have shown that ovine luteal tissue binds hCG with an affinity 3-30-fold higher than that of oLH. Secondly, we used luteal minces, as the conditions used to disperse luteal tissue (1) significantly reduced luteal LH receptor levels, possibly compromising steroidogenic response in vitro (T.A.…”
Section: Luteal Lh Responsiveness In Vitromentioning
confidence: 99%
“…A number of different mechanisms have been suggested to be responsible for the formation of inadequate luteal phases in sheep, including defective maturation of the preovulatory follicle (Keisler & Keisler 1989, Hunter et al 1986, White et al 1987, Southee et al 1988a, Khalid et al 1997, Lund et al 1999, Bartlewski et al 2001, perhaps due to an inappropriate pattern of LH stimulation of the follicle prior to the LH surge (McLeod et al 1982a, Wright et al 1983, attenuation of the LH surge (Bartlewski et al 2004), inadequate luteinization (Atkinson 1988, Hunter et al 1988, inappropriate luteal support of the new CL (Hunter et al 1988) and/or increased susceptibility to luteolytic stimuli (Hunter et al 1989, Beard & Hunter 1996 arising from the uterus (Southee et al 1988b, Hu et al 1991, though see Rahmanian and Murdoch 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LH, but not FSH, appears to be responsible for the induction of ovulation in seasonally anoestrous ewes treated with low doses of GnRH (McLeod et al, 1982(McLeod et al, , 1983McLeod & Haresign, 1987). Wallace & McNeilly (1986) In seasonally anoestrous ewes, a prolonged period of treatment with low doses of GnRH will consistently induce development of preovulatory follicles which culminates in ovulation (Hunter et al, 1986). In the current experiments, GnRH-treated seasonally anoestrous ewes were used to monitor the final stages of development of the preovulatory follicle.…”
Section: Introductionmentioning
confidence: 99%